Hydrogeological characteristics of the Lower Cretaceous terrigenous complex of the Karkinit-Northern Crimean deep in the aspect of its potential for oil and gas presence - Колодій, Іванна Володимирівна; Медвідь, Медвідь Богданівна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Purpose. To substantiate the prospects for oil and gas presence in the Lower Cretaceous sediments of the Karkinit-Northern Crimean deep based on hydrogeological (hydrogeochemical, gas-hydrogeochemical and geobaric) features. Methodology. Investigations of formation waters and water-dissolved gases were based on the methods of chemical, elementary spectral and gas chromatographic analyses executed at the laboratories of subsidiary joint-stock company "Chornomornaftogaz", subsidiary "Crimean Geology" and the Institute of Geology and Geochemistry of Combustible Minerals of NASU. For the comparison of formation pressure we applied the hydrostatic coefficient (Ch). Ch is the ratio of measured formation pressure to conditionally hydrostatic at the depth of the measuring with γ=1.000 (Рf/Рch), which eliminates the influence of uneven depths of measurement and different water densities, that is, to get the reduced value. For processing materials Excell, Corell Draw and Surfer are used. Results. Regional features of formation waters in the Lower Cretaceous complex as well as their chemical composition formation conditions are established. According to retrospective data analysis on the Crimean Plains, using the information received on the Black Sea shelf, we come to a conclusion that formation waters of the Lower Cretaceous complex are mainly sedimentogenic. The sulfate-natrium (S.Na) waters of the basal horizon and the Lower Cretaceous aquiferous complex most likely are infiltrative. This is evidenced by the decrease in the indicators of metamorphism of rCa/rMg, r(Cl-Na)/rMg and the increase in Cl/Br to over 1000, the lowered content of iodine (J) and bromine (Br). Infiltrative (paleoinfiltrative) waters mixed with primary sedimentogenic waters. This was accompanied by the decrease in their mineralization and thalassogenic trace elements contents in them. Modern infiltration from the land of meteoric waters at depths of more than 2000–3000 meters through the hydrodynamic barriers of the elision water drive system is impossible, but it could be realized at the continental infiltration stages of the foreground development and before the late Cretaceous time. This is evidenced by the continuous continental conditions marked by denudation of rocks. The main processes in the chemical composition formation of formation waters of Cretaceous and Lower Cretaceous complexes could have been: leaching rocks, mixing of infiltrative fresh or saline waters with thalassogenic waters; mixing of these waters with waters of the high temperature (>2000C) dehydration of clay rocks with formation of non-infiltrative (S.Na) and (Hyd.Car.Na) waters. Based on the analysis of the hydrostatic coeficient distribution (Ch) in the basal and Lower Cretaceous aquiferous complexes the existence of the elision water pressure system within the Karkinit-Northern Crimean deep is confirmed. The cause of overhydrostatic pressures is most likely to be the dehydration of clay rocks and the intrusion of deep gases. Geobaric conditions and filtration parameters suggest that the water flows of the elision water pressure system can move from the deepest parts of the Karkinit-Northern Crimean deep towards its sides. Originality and practical significance. The nature and forming conditions of formation waters have been substantiated. According to gas-hydrogeochemical and geobaric features it was possible to distinguish localities promising for hydrocarbon prospecting in the Lower Cretaceous deposits.